Gender, Metal and the Media Women Fans and the Gendered Experience of Music - Hill, Rosemary Lucy.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book is a timely examination of the tension between being a rock music fan and being a woman. From the media representation of women rock fans as groupies to the widely held belief that hard rock and metal is masculine music, being a music fan is an experience shaped by gender. Through a lively discussion of the idealised imaginary community created in the media and interviews with women fans in the UK, Rosemary Lucy Hill grapples with the controversial topics of groupies, sexism and male dominance in metal. She challenges the claim that the genre is inherently masculine, arguing that musical pleasure is much more sophisticated than simplistic enjoyments of aggression, violence and virtuosity. Listening to women's experiences, she maintains, enables new thinking about hard rock and metal music, and about what it is like to be a women fan in a sexist environment. .
1.Gender, Metal and the Media: An Introduction -- 2.Hard Rock and Metal as an Imaginary Community -- 3.The media and the imaginary community -- 4.Women Fans and the Myth of the Groupie -- 5.Listening to Hard Rock and Metal Music -- 6.Metal and Sexism -- 7.The Gendered Experience of Music .
Keywords: Music; Feminist anthropology; Media and Communication; Gender Studies